The Effects of Cardiometabolic Comorbidities on Biologic Treatment for Psoriasis with Respect to PASI Scores: A Qualitative Systematic Review - Osman A; Nigro A; Taylor AC; Saal R; Ormaza Vera A; Enos C (Dove Medical Press, 2024)
Alim Osman, Alexandra Nigro, Amanda Chen Taylor, Ryan Saal, Ana Ormaza Vera, Clinton Enos Department of Dermatology, Eastern Virginia Medical School, Norfolk, VA, USACorrespondence: Alim Osman, Department of Dermatology, Eastern Virginia Medical School, Norfolk, VA, USA, Email osmana@evms.eduObjective: Cardiometabolic risk factors have been shown to decrease biologic efficacy in patients treated for inflammatory conditions. The purpose of this systematic review is to provide a qualitative evaluation of studies investigating biologic response among psoriasis patients with cardiometabolic comorbidities.Methods: A comprehensive review was conducted according to the Preferred Reporting Guidelines for Systematic Reviews and Meta-Analysis guidelines to screen for studies including patients with cardiometabolic risk factors receiving biologic therapy for psoriasis. Studies not including a Psoriasis Area and Severity Index (PASI) score to evaluate treatment outcomes were not included. All studies underwent quality/bias analysis using the Methodological Index for Non-Randomized Studies (MINORS) scale.Results: Obesity and Body Mass Index (BMI) were the most studied cardiometabolic risk factors. The majority of the studies reported a lower frequency of achieving PASI75 and PASI90 response with increasing BMI/obesity rates. Diabetes and hypertension showed similar findings but were not studied as frequently. Hyperlipidemia and other lipid disorders were less frequently studied.Conclusion: Relationships between cardiometabolic risk factors and lower frequencies of achieving PASI75/90 exist in current literature. This qualitative systematic review reports evidence of lower PASI75 and PASI90 response rates in the presence of cardiometabolic risk factors.Keywords: psoriasis, cardiometabolic, obesity, PASI, hypertension, biologic